2014
DOI: 10.1177/1043659614527623
|View full text |Cite
|
Sign up to set email alerts
|

Insights From Health Care Professionals Regarding Palliative Care Options on South Dakota Reservations

Abstract: To address the health disparities of the NA population specific to palliative care, public health policy reform and education for health professionals are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…of articles Collaboration Community Engagement X [ 14 , 28 ] X [ 22 ] X [ 24 , 26 ] X [ 6 , 23 , 25 , 27 ] 9 Family Engagement X [ 14 , 31 ] X [ 32 – 34 ] X [ 24 , 30 ] X [ 25 , 27 , 29 ] 10 Health Care Provider Collaboration X [ 28 ] None identified None identified X [ 25 ] 2 Service Delivery Funding X [ 14 , 37 ] None identified None identified X [ 6 , 23 , 25 ] 5 Communication X [ 14 , 31 , 37 ] X [ 33 , 34 , 42 ] X [ 24 , 26 , 65 ] X [ 6 , 23 ] 11 Policy Change X [ 37 ] ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of articles Collaboration Community Engagement X [ 14 , 28 ] X [ 22 ] X [ 24 , 26 ] X [ 6 , 23 , 25 , 27 ] 9 Family Engagement X [ 14 , 31 ] X [ 32 – 34 ] X [ 24 , 30 ] X [ 25 , 27 , 29 ] 10 Health Care Provider Collaboration X [ 28 ] None identified None identified X [ 25 ] 2 Service Delivery Funding X [ 14 , 37 ] None identified None identified X [ 6 , 23 , 25 ] 5 Communication X [ 14 , 31 , 37 ] X [ 33 , 34 , 42 ] X [ 24 , 26 , 65 ] X [ 6 , 23 ] 11 Policy Change X [ 37 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the literature, the need to collaborate and to engage meaningfully with communities [ 6 , 14 , 22 28 ] and families [ 14 , 24 , 25 , 29 34 ] before designing and implementing any program was highlighted as a fundamental prerequisite for progress. Most of the studies were conducted in rural or remote locations where EOL care provisions were often not well-developed or well-understood.…”
Section: Resultsmentioning
confidence: 99%
“…A large analysis of racial/ethnic disparities in palliative care in hospitals that served either majority white, mixed, or majority minority patients found that stroke patients of any race/ethnicity were less likely to receive palliative care in a mixed or majority minority hospital (Faigle et al, 2017). The only two studies that examined palliative care for American Indians/Alaskan Natives found that rural care settings were underresourced for culturally competent, accessible palliative care for this population (Isaacson et al, 2015; Isaacson & Lynch, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…One study asked white, African American, and Hispanic patients if they had ever heard of palliative care, and those who had were more likely to be white and have higher education and income levels (Matsuyama et al, 2011). Mistrust of the medical system was cited in studies of American Indians (Isaacson et al, 2015) and African Americans, particularly strong in African American males (Duffy et al, 2006). These findings were echoed by palliative care providers who noted that mistrust of providers and lack of information on palliative care were strong deterrents to receiving high-quality end-of-life care in the African American community (Rhodes et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation